2014
DOI: 10.1038/nsmb.2741
|View full text |Cite
|
Sign up to set email alerts
|

EttA regulates translation by binding the ribosomal E site and restricting ribosome-tRNA dynamics

Abstract: Cells express many ribosome-interacting factors whose functions and molecular mechanisms remain unknown. Here, we elucidate the mechanism of a newly characterized regulatory translation factor, Energy-dependent Translational Throttle A (EttA), which is an Escherichia coli representative of the ATP-binding cassette F (ABC-F) protein family. Using cryo-EM, we demonstrate that the ATP-bound form of EttA binds to the ribosomal tRNA exit (E) site, where it forms bridging interactions between the ribosomal L1 stalk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
177
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(192 citation statements)
references
References 70 publications
(147 reference statements)
15
177
0
Order By: Relevance
“…Two new reports describe the discovery of a bacterial protein factor, energy-dependent translation throttle A (EttA), which can regulate translation in response to changes in cellular energy homeostasis 1 , 2 . The ability of EttA to link protein synthesis to changing metabolite levels opens up the exciting possibility that other translation factors might also respond to different physiological cues, as is the case for transcriptional regulation.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Two new reports describe the discovery of a bacterial protein factor, energy-dependent translation throttle A (EttA), which can regulate translation in response to changes in cellular energy homeostasis 1 , 2 . The ability of EttA to link protein synthesis to changing metabolite levels opens up the exciting possibility that other translation factors might also respond to different physiological cues, as is the case for transcriptional regulation.…”
mentioning
confidence: 99%
“…1 report the X-ray crystal structure of nucleotide-free EttA at 2.4-Å resolution ,and Chen et al 2 report the cryo-EM structure of a mutant version of EttA bound to the ribosome. This EttA mutant (E188Q E470Q, termed EttA-EQ 2 ) is a key tool in the present studies because it is able to bind, but not hydrolyze, ATP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that ARE proteins might interact with the ribosome and affect the binding of antibiotics to their target site (17). Very recently, the function of the first ABC-F protein, EttA, as a translation factor which regulates protein synthesis depending on cell energy status has been characterized (19,20). The similarity of Vga(A)* to EttA (31% identity) allows us to envisage a mechanism of Vga(A) action based on the EttA one, providing a more-detailed insight into the probable involvement of Vga(A) in antibiotic resistance by ribosome protection than ever before.…”
mentioning
confidence: 99%